Nanotechnological Solutions For Controlling Transmission And Emergence Of Antimicrobial-Resistant Bacteria, Future Prospects, And Challenges: A Systematic Review - Ssekatawa, Kenneth; Byarugaba, Dennis K.; Kato, Charles D.; Ejobi, Francis; Tweyongyere, Robert; Lubwama, Michael; Kirabira, John Baptist; Wampande, Eddie M. (Journal of Nanoparticle Research, 2020)
Globally, a high prevalence of multi-drug-resistant (MDR) bacteria, mostly methicillin-resistant Staphylococcus aureus and carbapenem-resistant Enterobacteriaceae, has been reported. Infections caused by such bacteria are expensive and hard to treat due to reduced efficient treatment alternatives. Centered on the current rate of antibiotics production and approvals, it is anticipated that by 2050 up to 10 million people could die annually due to MDR pathogens. To this effect, alternative strategies such as the use of nanotechnology to formulate nanobactericidal agents are being explored. This systematic review addresses the recent approaches, future prospects, and challenges of nanotechnological solutions for controlling transmission and emergence of antibiotic resistance. A comprehensive literature search of PubMed and BioMed Central databases from June 2018 to January 2019 was performed. The search keywords used were “use of nanotechnology to control antibiotic resistance” to extract articles published only in English encompassing all research papers regardless of the year of publication. PubMed and BioMed Central databases literature exploration generated 166 articles of which 49 full-text research articles met the inclusion guidelines. Of the included articles, 44.9%, 30.6%, and 24.5% reported the use of inorganic, hybrid, and organic nanoparticles, respectively, as bactericidal agents or carriers/enhancers of bactericidal agents. Owing to the ever-increasing prevalence of antimicrobial resistance to old and newly synthesized drugs, alternative approaches such as nanotechnology are highly commendable. This is supported by in vitro, ex vivo, and in vivo studies assessed in this review as they reported high bactericide efficacies of organic, inorganic, and hybrid nanoparticles.
Keywords: Multidrug resistance . Inorganic nanoparticles . Organic nanoparticles . Nanohybrid . Nanocarriers . Cytotoxicity . Nanomedicine